REVELATION AS AN INTERPERSONAL DIALOGUE BETWEEN GOD AND HUMAN BEINGS: A Comparative Study of the Theology of Revelation according to Karl Rahner and the Second Vatican Council with a Selective Reception Analysis - Puthumattathil, Shinto George (Asian Horizons, 2017)
This study investigates to what degree Karl Rahner’s theology of existential experience is a sufficient means to help understand the theology of revelation developed at the Second Vatican Council. The contexts that shaped this study are those of the institutional reinterpretation of Vatican II’s paradigm shifts in the theology of revelation on account of a conservative agenda and the subsequent insistence at the fiftieth anniversary celebrations for rediscovering the true objective and the different dimensions of the theology of revelation developed at Vatican II. This study does not try to prove by historical research that any of the twenty six articles of Dei verbum is an exclusive contribution by Rahner. Rather, it is a comparative analysis in view of demonstrating the theological parallelism. We have undertaken this study in three parts, each of which is further divided into two sections based on the hypothesis that the Vatican II paradigm shifts in the theology of revelation significantly owe to the Rahnerian objectives and dimensions of the theology of revelation.